Sports Pharmacology: A Medical Pharmacologist’s Perspective - Malve, Harshad O. (J Pharm Bioallied Sci, 2018)
Abuse of substances or methods to enhance the performance is becoming very common in the sports, which often destroys the spirit of competition. The regulatory bodies for sports have reported rates ranging from 5% to 31% for the use of performance-enhancing substances among athletes. Athletes can have serious injuries and morbidities, leading to poor health with the use of such substances. Commonly abused agents in sports include anabolic–androgenic steroids and its analogs, blood, erythropoietin, growth hormone and its derivatives, nutritional supplements, creatine, amphetamines, beta-hydroxy-beta-methylbutyrate (HMB), stimulants, and analgesics. Health-care professionals need to be careful while prescribing medicines to sportspersons. Knowledge of exercise physiology, pharmacology of the commonly used agents for sports-related injuries, and agents used for doping could help the sportspersons and health-care professionals to avoid the embarrassment arising because of misuse of these agents. Sports pharmacology includes study of the various aspects of the drug use and abuse in sports and treatment of sports-related injuries. Focusing on sports pharmacology in the medical curriculum can help the upcoming health-care professionals to support the sportspersons to improve the quality of their life by using various drugs and other substances within the standardized limits and avoid embarrassment of doping.